Responses of traditional and improved upland rice culttvars to different moisture regimes - Pereira, José Almeida; Sobrinho, José Tavares; Beltrão, Napoleão Esberard de M. (Pesquisa Agropecuaria Brasileira, 1994)
A greenhouse experiment was carried out in Areia, Paraíba, PB, Brazil, to evaluate responses of two traditional (Cáqui and Vermelho) and two improved (IAC 165 and Guarani) upland rice (Oriza sativa L.) cultivars to four soil moisture regimes (60-70%, 70-80%, 80-90% and 90-100% of the field capacity). The experimental design was completely randomized in a 4 x 4 factorial arrangement with four replications. The growth and yield parameters evaluated were: leaf area, 1,000 grains weight, panicle length, panicle number, spikelet/panicle number, grain yield, root dry weight, shoot dry weight, total dry matter and harvest index. All parameters studied were significantly affected by moisture regimes except 1,000 grains weight and harvest index. The improved cultivar IAC 165 was the one that less decreased the grain yield and the total dry matter, but the traditional ’Vermelho’ was the one that showed the largest genetic potential under moisture regime more unfavorable.